2022
DOI: 10.1007/s13300-022-01332-x
|View full text |Cite|
|
Sign up to set email alerts
|

Addendum 1: Forum for Injection Technique and Therapy Expert Recommendations, India

Abstract: With the emerging complexities in chronic diseases and people's lifestyles, healthcare professionals (HCPs) need to update their methods to manage and educate patients with chronic lifestyle disorders, particularly diabetes. The insulin injection technique (IIT), along with various parameters, must also be updated with newer methods. Forum for Injection Technique and Therapy Expert Recommendations (FIT-TER), India, has updated its recommendations to cover newer ways of detecting hypoglycaemia and lipohypertrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Therefore, storing insulin and injection pens at the proper temperature and location is mandatory knowledge for participants. 14 Furthermore, our study also showed that 62.9% of participants responded that they usually stored insulin pens without removing the tip of the used needle after taking a shot. Heinemann, 12 writing on the importance of good insulin injection practices in DM management, suggested not storing insulin pens with needles after use.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Therefore, storing insulin and injection pens at the proper temperature and location is mandatory knowledge for participants. 14 Furthermore, our study also showed that 62.9% of participants responded that they usually stored insulin pens without removing the tip of the used needle after taking a shot. Heinemann, 12 writing on the importance of good insulin injection practices in DM management, suggested not storing insulin pens with needles after use.…”
Section: Discussionmentioning
confidence: 54%
“…Failure to remove the tip of a used needle after injection can lead to bacterial infection, air leakage, and drug leakage. 14 In this study, 71.2% of participants knew to store pens and insulin in the refrigerator but not to freeze them. As mentioned above, unused insulin pens must be stored properly to retain the best quality of the drug before being injected into the body.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations